Secondary Students’ Emotional Engagement In Role Play Assissted Speaking Classroom - Afiyanti, Widiya; Ridwan, Iwan; Rahmawati, Maya (Jurnal Ilmiah Wahana Pendidikan, 2023)
The objectives of this research is to explore how far students' emotional engangement when learning speaking using the role play method. This research is a qualitative research. The sample of this research is five students from eight grade of Junior High School in Karawang. The data were gathered by using observasion and interview. The data were analysed by thematic analysis. The findings showed that students have positive emotional engangement such as enjoyment, happiness, and confidence. Students also experience negative emotions such as boredom, frustration, and anxiety. In conclusion, positive emotional engangement in students indicates that students still have the desire and enthusiasm in facing difficulties during the learning process so that they are able to more understand the learning material. Negative emotional involvement indicates the lack of interest in students towards learning processes and materials, so it makes students difficult to focus and understand learning material.